1988
DOI: 10.1021/ic00292a008
|View full text |Cite
|
Sign up to set email alerts
|

Redox properties and ligand loss chemistry in aqua/hydroxo/oxo complexes derived from cis- and trans-[(bpy)2RuII(OH2)2]2+

Abstract: Electrochemical studies on the cis and trans isomers of [ (bpy) 2Run(OH2)2]2+ (bpy is 2,2'-bipyridine) as a function of pH in aqueous solution have revealed the existence of a series of pH-dependent redox couples that interconvert oxidation states II -VI. The electrochemical data give insight into the relative stabilities of the cis and trans isomers as well the stabilities of individual oxidation states. In acidic solution, oxidation state VI for the cis complex is unstable with respect to ligand loss and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 1 publication
9
94
0
2
Order By: Relevance
“…A rapid two-electron oxidation of the resulting Ru II complex would afford a (TrpyO)Ru IV (L)(LЈ)(LЉ) complex where (TrpyO) Ϫ is the hydroxylated (and deprotonated) terpyridine ligand and L, LЈ, LЉ are oxo, hydroxyl, aquo, and/ or chloro ligands. The oxidation chemistry of (Bpy) 2 Ru II (OH 2 ) 2 2ϩ and (Trpy)Ru II (OH 2 ) 3 3ϩ suggests that the high oxidation state of the catalytic species will likely encourage one or more of its ligands to be oxo groups [16,17]. Since reported dimeric and trimeric polypyridine ruthenium complexes all exhibit strong absorption peaks at 600 nm and longer [18], the 472 nm absorption of the catalytic species seems characteristic of a monomer.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid two-electron oxidation of the resulting Ru II complex would afford a (TrpyO)Ru IV (L)(LЈ)(LЉ) complex where (TrpyO) Ϫ is the hydroxylated (and deprotonated) terpyridine ligand and L, LЈ, LЉ are oxo, hydroxyl, aquo, and/ or chloro ligands. The oxidation chemistry of (Bpy) 2 Ru II (OH 2 ) 2 2ϩ and (Trpy)Ru II (OH 2 ) 3 3ϩ suggests that the high oxidation state of the catalytic species will likely encourage one or more of its ligands to be oxo groups [16,17]. Since reported dimeric and trimeric polypyridine ruthenium complexes all exhibit strong absorption peaks at 600 nm and longer [18], the 472 nm absorption of the catalytic species seems characteristic of a monomer.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for radical coupling to occur is reaching the Ru V =O complex in the catalytic cycle [24]. While at higher pH, it was shown that only the cis isomer is stable in the Ru V =O configuration, both are able to reach Ru V at pH 1.0 [17] , where this experiment occurred. If the radical coupling mechanism is taking place for the cis-isomer and not the trans-isomer, it would explain the difference in catalytic activity, as this pathway corresponds to a high rate of oxygen production.…”
Section: Electron Paramagnetic Resonance Measurementsmentioning
confidence: 96%
“…Both cis-and trans-[Ru(bpy) 2 (H 2 O) 2 ] 2+ were reported and characterized by Meyer et al [16,17]. It was found that the cis configuration is more stable in the absence of light, but under illumination the complex undergoes cis-trans isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…36 We prepared the complex in,in-{[Ru II (trpy)(H 2 O)] 2 (µ-bpp)} 3+ , 2; the process consisted of dinucleating 3,5-bis(2-pyridyl)pyrazolate anionic ligand (bpp − ) that acts as a backbone (see Scheme 1) for the Ru metal centers, placing them in close proximity and further providing a route for electronic coupling between them as shown in Figure 4(a). In addition, the ancillary trpy ligands occupy three meridional positions in such a way that the sixth coordination is occupied by oxygen atoms of aquo groups.…”
mentioning
confidence: 99%